PP.24.10: ABNORMAL WATER BALANCE AND KIDNEY FUNCTION DURING PREGNANCY IN THE STROKE PRONE SPONTANEOUSLY HYPERTENSIVE RAT. (June 2015) - Small, H.; Morgan, H.; Delles, C.; Graham, D.
Abstract : Objective: Previously, we have shown that the SHRSP has deficient uterine artery remodelling in response to pregnancy relative to the normotensive WKY. However, the kidney function during pregnancy in these animals has yet to be described. Design and method: Metabolic cage data was collected at pre-pregnancy then at gestational days (GDs) 6, 12 and 18 from WKY (n = 9) and SHRSP (n = 9). Animals were sacrificed on day 18. Urinary electrolytes, glucose, creatinine and urea were analysed by Cobas c311/501 analyzer. Biomarkers were analysed using ELISA. Results: Throughout pregnancy, SHRSP had a significantly reduced urinary output (GD18 14.65 ± 3.77 vs. 28.44 ± 2.05 ml/24 hours) and fluid retention (GD18 10.81 ± 1.05 vs. 17.06 ± 2.09 ml/24 hours). In human pregnancy, approximately 25% weight gain is due to water retention. Accordingly, SHRSP had a significant reduction in both pregnancy dependent (56.66 ± 3.77 vs. 84.53 ± 3.34 g) and independent [total weight gain minus weight of the uterine horn] (35.94 ± 5.23 vs. 59.12 ± 2.89 g) weight gain. Analysis of 24 hour urine samples showed no significant difference in electrolytes at pre-pregnancy but became significantly increased in the SHRSP at GD18 (Na [2.66 ± 0.09 vs. 1.43 ± 0.07 mmol/L], K [10.56 ± 1.23 vs. 3.43 ± 0.19 mmol/L] and Cl [6.33 ± 0.46 vs. 2.11 ± 0.12 mmol/L]). Similarly, creatinine (GD18 0.25 ± 0.01 vs. 0.12 ± 0.01 mmol/L) and urea (GD18 34.52 ± 3.47 vs. 9.85 ± 0.55 mmol/L) were also significantly increased during pregnancy. An increase in Tnf excretion at day 12 (31.75 ± 2.84 vs. 20.59 ± 1.96 pg/ml) suggests that there may be an inflammatory process present in the kidney which underlies the aforementioned changes. Conclusions: In conclusion, we have seen pregnancy specific increases in a number of urinary markers in the SHRSP. These modest but significant increases indicate that there may be a moderate dysfunction of the kidney during pregnancy. This preliminary data needs to be supported by measurement of GFR and kidney histology.